TO STUDY THE ROLE OF VAMAN KARMA IN PATHOGENESIS PCOD (POLYCYSTIC OVARIAN DISEASE) (International Journal of Ayurveda and Pharma Research, 2020)
PCOD is a common gynecological problem in fertile age group of women which includes hormonal imbalance, weight gain and disturbed menstrual cycle. PCOD can be correlated with ‘Granthi’ described in ayurveda on the basis of pathogenesis and aetiology. Ayurveda suggested Vamana Karma (Initiate vomiting by medicinal drugs) for treatment of Granthi. According to Ayurveda Samhita (classic text) pathogenesis of Granthi is due to vitiation of Kapha dosha and Meda dhatu. On comparison with modern science all the etiological factors of PCOD are same as factors responsible for vitiation of Kapha dosha and Meda dhatu like sedentary life style, excessive consumption of fast foods, day sleep etc. Vaman karma also corrects vitiated Kapha dosha and Meda dhatu. Hence Vaman Karma can be very beneficial in treatment of PCOD patients. Clinical study of 20 patients of PCOD of fertile age group of women is carried in Anand Ayurved College. Patients are treated with Vaman karma along with Ayurvedic medicine and exercise for three months. Study shows significant positive changes in pathogenesis of patients. Vaman karma also corrects hormonal imbalance in much extent. Weight loss and menstrual regularity are observed in patients. Thus Vaman karma can be proven as a landmark treatment in PCOD along with Ayurveda medicine, diet and exercise.